EQUINE THERMOREGULATORY RESPONSES DURING SUMMERTIME ROAD TRANSPORT AND STALL CONFINEMENT - GREEN, ANGELA R.; GATES, RICHARD S.; LAWRENCE, LAURIE M. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Thermoregulatory responses of horses subjected to summer-time road transport and stall confinement were investigated in this study. Six mature geldings were transported 168 km in a 4-horse trailer and were monitored while tethered in their stalls, on alternate days. Core body temperature (GT) demonstrated negligible response during transport, but GT following transport was higher than GT for non-transport. GT tended to increase with increased temperature humidity index (THI). THI within the trailer was greatest for positions near the front, and was influenced by daily weather which varied over experiment days from heat stress conditions to moderate discomfort.